Kajian Teologis Tentang Politik Identitas dalam Pemilihan Kepala Daerah Tahun 2020 dan Dampaknya Pada Jemaat - Garera, Martha; Masambe, Helen Gratia (Educatio Christi, 2024)
The purpose of this study is to find out exactly what identity politics is and especially to know the practices of identity politics in the 2020 election of regional heads in South Minahasa Regency and its impact in the life of the GMIM Efrata Pinamorongan congregation. Basically, this study wants to re-examine the understanding of politics from the congregation, especially which has deviated from the basis and purpose of politics, which is to provide common welfare. In this study, the author uses a qualitative research method by collecting research data based on observations, interviews, and literature studies. And the results of the study show that the GMIM Efrata Pinamorongan congregation is involved in the practice of identity politics.